Reports of Conferences, Institutes, and Seminars. Issue 3 (2nd October 2017) - Kimbrough, John; Knabe, Ian; LaBrie, Jessica K.; Purtee, Sharon A.; Ray, Emily; Twardowski, Kristen; Rogers-Collins,, Karen
ABSTRACT: This quarter's column reports on sessions from NASIG 2017: Racing to the Crossroads, held in Indianapolis, IN, June 8 to 11, and ALA Annual 2017: Transforming Our Libraries, Ourselves, which took place in Chicago, IL, June 22–27.